Thrombin as important factor for cutaneous wound healing: Comparison of fibrin biomatrices in vitro and in a rat excisional wound healing model. Issue 6 (8th January 2015) - Gugerell, Alfred; Pasteiner, Waltraud; Nürnberger, Sylvia; Kober, Johanna; Meinl, Alexandra; Pfeifer, Sabine; Hartinger, Joachim; Wolbank, Susanne; Goppelt, Andreas; Redl, Heinz; Mittermayr, Rainer
Abstract Fibrin biomatrices have been used for many years for hemostasis and sealing and are a well‐established surgical tool. The objective of the present study was to compare two commercially available fibrin biomatrices regarding the effect of their thrombin concentration on keratinocytes and wound healing in vitro and in vivo. Keratinocytes showed significant differences in adhesion, viability, and morphology in the presence of the fibrin matrices in vitro. A high thrombin concentration (800–1, 200 IU/mL) caused deteriorated cell compatibility. By using a thrombin inhibitor, those differences could be reversed. In a rat excisional wound healing model, we observed more rapid wound closure and less wound severity in wounds treated with a fibrin matrix containing a lower concentration of thrombin (4 IU/mL). Furthermore, fewer new functional vessels and a lower level of vascular endothelial growth factor were measured in wounds after 7 days treated with the matrix with higher thrombin concentration. These in vivo results may be partially explained by the in vitro biocompatibility data. Additionally, results show that low thrombin biomatrices were degraded faster than the high thrombin material. Hence, we conclude that the composition of fibrin biomatrices influences keratinocytes and therefore has an impact on wound healing.